Hubungan Antara Profil Pemakaian Sepatu dengan Keluhan Plantar Heel Pain (PHP) pada Karyawan Wanita di Rumah Sakit Bhayangkara Polisi Daerah Lampung - Nurlaili Wardah Humairoh; Helmi Ismunandar; Sutarto; Rani Himayani (CV. Jasa Sukses Abadi, 2026)
Plantar heel pain is a common musculoskeletal complaint among female workers, particularly in workplaces that require prolonged standing, walking, and the use of formal footwear. Biomechanical factors such as duration of shoe use, heel height, and body mass index are believed to increase mechanical stress on the plantar fascia and contribute to heel pain, yet evidence in Indonesia remains limited. This study aimed to examine the relationship between shoe-wearing profiles and body mass index with plantar heel pain among female employees at Bhayangkara Hospital, Lampung Regional Police, using an analytic observational design with a cross-sectional approach. A total of 120 participants were selected through purposive sampling. Plantar heel pain was assessed using the Plantar Fasciitis/Disability Scale questionnaire, body mass index was obtained through anthropometric measurements, and heel height was measured directly. Data were analyzed using univariate and bivariate methods with Spearman correlation tests at a significance level of p < 0.05. The results showed a relatively high prevalence of plantar heel pain among participants, with a significant association between duration of shoe use and plantar heel pain, while heel height and body mass index were not significantly associated, indicating that prolonged shoe use is the main contributing factor in practice.